Effect of the Addition of Soy Beverage and Propionic Bacteria on Selected Quality Characteristics of Cow’s Milk Yoghurt Products - Małgorzata Ziarno; Dorota Zaręba; Wiktoria Dryzek; Rozeta Hassaliu; Tomasz Florowski (Applied Sciences, 2022)
Many diet trends have emerged over the last few years, including plant-based diets with soya as an important component, while fermented milk beverages have been an integral part of the human diet for thousands of years. However, there is little research on the potential of using propionic bacteria for dairy or plant-based food fermentation. The aim of this study was to evaluate the effects of soy beverage addition and propionic bacterium application on the quality of dairy yoghurt products. Three variants of the products—based on cow’s milk, soya beverages, and mixtures of both—were prepared and then fermented with yoghurt bacteria, propionic bacteria or a mixture thereof. It was found that it is possible to obtain functional yoghurt products based on cow’s milk, as well as milk–soya blends, using a mixture of yoghurt and propionic cultures. The resulting milk, milk–soya, and soya yoghurt products displayed pH values in the correct range and a stable bacterial population during refrigerated storage for 21 days. The refrigerated storage time and the type of culture starter used significantly determined the quality characteristics of the milk, milk–soya and soya yoghurt products, such as their firmness, adhesiveness, and water-holding capacity.